External validation of a multivariate model for predicting the risk of death in patients with chronic heart failure and an implantable cardioverter – defibrillator - N. B. Lebedeva; P. G. Parfenov; A. P. Egle; V. I. Ivanov; Yu. V. Galintsev; V. V. Kashtalap; O. L. Barbarash (Бюллетень сибирской медицины, 2024)
Aim. To perform external validation of a multivariate model for predicting the risk of death in patients with an implantable cardioverter – defibrillator (ICD) in an independent sample. Materials and methods. The group for model development included 260 patients from the Implantable Cardioverter – Defibrillator Patient Registry who had an ICD implanted between 2015 and 2019. External validation of the model was carried out in an independent, prospective, observational cohort study of patients from the same registry, in whom an ICD was implanted between 2020 and 2021, a total of 94 patients, median age 66 (52;73) years, 73 (77.6%) men, 21 (22.4%) women. In 89 (94.7%) patients, an ICD was implanted for primary prevention of sudden cardiac death. Following a telephone survey and examination of medical records from hospital and clinic databases, data on the vital status (alive / dead) and causes of death were obtained during a 2.5-year follow-up. The actual and predicted mortality from the estimated multivariate model were compared. Results. During the follow-up, a total of 26 (27.7%) patients died in the external validation group, which was comparable to the development group (p > 0.05). In the group of deceased, 15 (57.7%) people developed acute decompensated heart failure, 4 (14.8%) had myocardial infarction, 6 (23.1%) had pneumonia caused by a new coronavirus infection, and one (3.8%) patient died due to an infectious complication. The diagnostic accuracy of the multivariate model for predicting the risk of death in patients with ICD in an independent sample was sufficient (the area under the curve (AUC) of the created model was 0.8). The sensitivity of the model was 76.2%, specificity – 76.1%. Previously, in the development cohort, AUC of the created model was 0.8, the sensitivity of the model was 75.7%, and the specificity was 80%. Model significance did not differ significantly between the development and external validation groups (p = 0.102, McNeil test).Conclusion. The multivariate prediction model has sufficient statistical power to predict the risk of long-term death after ICD implantation, which was externally validated.